El portafolio digital ¿Una herramienta para aprender a ser docentes críticos?: Un estudio de casos - Muñoz González, Laura de la Concepción; Soto Gómez, Encarnación (Universidad de Costa Rica, 2019)
The purpose of this article is to share the pedagogical opportunities of the digital portfolio as a resource for teaching, learning and assessment during initial teacher training, especially in terms of developing skills to meet the educational challenges of the 21st century. A case study (2015-2019) focused on a group of 60 Early Childhood Education students from the University of Malaga (Spain) and 4 teachers, through a mixed design for the collection of information. In this sense, qualitative and quantitative analysis, saturation and triangulation of the data collected through observations, interviews, closed and open questionnaires, as well as focus groups determined initial and final categories. As results, it was found, firstly, that the digital portfolio is a tool that contributes to clarifying the need to establish a shared definition for its use and, secondly, recognizes its potential to promote awareness and construction of one's own knowledge, the reconstruction of practical thinking, the development of professional teaching skills and integral evaluation. The scope of this research can help to promote the study of good evaluation practices in the university, the necessary technological updating, as well as the application of methodological strategies that favor the development of teaching skills adapted to the information and knowledge society..